Regarding the role of rock paintings in studying the spiritual and religious life of ancient people - Tugalov Boburjon Bakhodir; Ummatov Sardar Kahramon; Bozorova Maftuna Toir (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, an attempt was made to reveal information about the role of stone paintings in the study of the spiritual and religious life of ancient people based on the data studied and scientifically analyzed by scientists